Research on generating secondary safety measure ticket for intelligent substation based on fuzzy learning - JI Peng; LI Yinghua; LI Yang; DANG Qi; ZHANG Chenyang (Diance yu yibiao)
In response to the problem that the accuracy and safety of traditional safety isolation methods cannot meet the requirements, an intelligent substation secondary safety measure ticket generation system is designed in this paper. This paper describes the principle of the secondary system strategy for intelligent substations, the rules for generating safety measures, and the construction of an expert database. It introduces the overall architecture of the secondary safety isolation system for intelligent substations, including model management layer, operation support layer, and production management layer. A fuzzy matrix between the symptom vector of safety measures and the cause vector of safety measures is established, safety measures are generated through fuzzy learning inference, and proposes rules for automatic generation of safety measures tickets. Finally, practical application in a certain region has proven that the designed system has improved correctness and security by 3.7% and 14.3% respectively compared to traditional security isolation methods.